Synthesis and Diatropicity of trans-N-Cyclohexyl-2′,5′,10b,10c-tetramethyl-pyrrolo[3,4-e]-10b,10c- dihydropyrene. the First Example of an Iso[17]annulenopyrrole - Lai, Y.-H. (2014)
Journal of Organic Chemistry